IMPACT ASSESSMENT OF AGE ON PROFESSIONAL STRESS OF ACTUARIAL AND INSURANCE EDUCATORS IN INDIA - SUBHRANSU SEKHAR JENA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
Irrespective of discipline and trade-boundaries, pedagogy of Insurance Education demands specialty in most of the cases. Teachers’ style of teaching [rather to assist in the process of learning] accords influence of sequels of factors and variables some of which may be clubbed under ‘psychopedagogical attributes’. Among the many other factors, these include professional-interest, job-satisfaction, collectivism and professional- stress. The present study attempts to explore the level and interrelationship of these psycho pedagogical attributes as apparent among the female educators from selected states of eastern-India. Attempt was also made to explore the impact of age of the female educators over these psychoeducational-attributes. Findings of the study reveal that age of the respondents possesses significant impact over the major psychopedagogical attributes viz., professional-interest, job-satisfaction, collectivism and professional- stress.